A irretroatividade das alterações jurisprudenciais no âmbito tributário - Silva, Daniel Souza Santiago da (2011)
The aim of the present dissertation is the study of the non-retroactivity of modifications of precedents set in the tax sphere, whose relevance is highlighted in view of the recent constitutional reforms as well as procedural legislation, which award great importance to precedents, generalizing the effects of decisions uttered in individual lawsuits. The work was divided in four chapters. In the first one, there is an analysis of the function of Law, the language through which it is expressed and the way to create the legal norm, which is differentiated from legal texts, concluding that the Judiciary Branch does not perform a mere operation of syllogism and deduction, but a true creation of sense and reach of prescriptive statements, concretizing rules from generalizing concepts applied by legislators. In the second chapter, there is a study of the issue of setting the precedent, determining criteria for the characterization of consolidated precedents, which, in spite of being able to orient the conducts in a generalized manner, will always be subject to modifications, as a way to preserve modernization, adequacy and improvement of the legal system. Subsequently, in the third chapter, there is a verification of categorization of the non-retroactivity as a rule to be applied in order to preserve the principle of legal certainty, of mandatory compliance in cases of characterization of a material alteration of law, that is, when there is a modification of the sense it was applied, even if there is no alteration of the legal text. Finally, the fourth chapter is intended to the analysis of situations of applied tax law and the necessary modulation of the effects of decisions that imply modification of the normative judicial expectations